2015
DOI: 10.1111/hpb.12430
|View full text |Cite
|
Sign up to set email alerts
|

What to expect when you're expecting a hepatopancreatobiliary surgeon: self-reported experiences of HPB surgeons from different training pathways

Abstract: Fellowship training in HPB surgery varies by training pathway. Training in MIS and ultrasound is deficient in each pathway. The ultimate scope of non-transplant HPB practice appears similar across training pathways. Thus, training pathway choice is best guided by the training experience desired and non-HPB components of anticipated practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…11 These offer variable experiences in pancreas, liver and biliary cases, and each pathway offers unique training foci. 12 In this study, an AHPBA rather than a SSO fellowship was the preferred pathway for residents who seek training in HPB surgery. Our study found that the type of fellowship pathway chosen by residents for HPB training depends on who performs these cases at host institutions.…”
Section: Discussionmentioning
confidence: 94%
“…11 These offer variable experiences in pancreas, liver and biliary cases, and each pathway offers unique training foci. 12 In this study, an AHPBA rather than a SSO fellowship was the preferred pathway for residents who seek training in HPB surgery. Our study found that the type of fellowship pathway chosen by residents for HPB training depends on who performs these cases at host institutions.…”
Section: Discussionmentioning
confidence: 94%
“…2 Historically, the path to a HPB-focused surgical practice involved completion of an apprentice-like model or, more recently, completion of a surgical oncology or transplant surgery fellowship. 3 A fourth pathway-completion of a HPB surgery fellowship-has been developed over the last decade, in response to increasing trends in subspecialization. 4 Among these pathways, there may be significant variation in terms of programmatic emphases and operative exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Less standardized apprenticeship training models at a variety of institutions have also offered a pathway to HPB surgery for surgical trainees in years past. 3 More recently, formal HPB surgery fellowships-created and accredited through a collaboration between the Fellowship Council (FC) and Americas Hepato-Pancreato-Biliary Association (AHPBA)-now offer another pathway to specialization in HPB surgery. 4 The curricula and foci among these three training programs vary considerably within North America, and there is even further heterogeneity globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fellows are able to inform potential deficiencies in breadth of training. 9 Separately, there appears to remain some disparity between the perceptions of programme directors and fellows regarding operative ability to undertake certain index complex cases, with fellows reporting lower confidence. 10 Consideration of this may help inform decisions on index caseload as there are no strong data on minimum case numbers, although it has been reported that 20 pancreatectomies are required for equivalence in mortality rates and 60 for equivalence in morbidity rates.…”
mentioning
confidence: 99%